The Application of Developmentally Appropriate Practice Learning Strategies to Improve Students' Arabic Learning Outcomes - Ade Arip Ardiansyah; Nanang Kosim; Aini Deo Rahmi Sudiana; Aziz Firmansyah; Abdelhak Belabed (PPPBA, 2024)
This study aims to evaluate the effect of using Developmentally Appropriate Practice (DAP) learning strategies with Index Card Match media on student learning outcomes in mufradāt material in class VIII-B MTs. This research is a classroom action research. In this study, 31 class VIII-B students of MTs Ar-Rasyidiyah were divided into five groups. Learning outcomes data is measured using multiple-choice tests and descriptions that are relevant to the mufradāt material. Data analysis using the t-test showed that students who used the DAP learning strategy with Index Card Match media experienced a significant increase in learning outcomes compared to conventional methods. This study concluded that the application of the DAP learning strategy with Index Card Match media could improve student learning outcomes on mufradāt material in class VIII-B MTs Ar-Rasyidiyah, with the acquisition of an average score on the pretest of 66 and an average score on the post-test of 99. Follow-up studies can involve larger samples and different learning materials to generalize these findings further. This research provides valuable insights into effective teaching strategies and highlights the importance of incorporating appropriate media to enhance student learning outcomes.